2012
DOI: 10.1113/jphysiol.2012.240267
|View full text |Cite
|
Sign up to set email alerts
|

The time course of the adaptations of human muscle proteome to bed rest and the underlying mechanisms

Abstract: Key points• It is still debated whether an imbalance between production and removal of reactive oxygen species is a major trigger of disuse skeletal muscle atrophy in human limb muscles and what the underlying mechanisms are.• In the bed rest model of human disuse, redox imbalance, impairment of antioxidant defence systems and metabolic derangement occurred early, before vastus lateralis muscle atrophy developed, and persisted through 35 days of bed rest.• Down-regulation of PGC-1α, a master controller of musc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
153
4
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 162 publications
(176 citation statements)
references
References 88 publications
17
153
4
2
Order By: Relevance
“…Similar results have been found in estivating toads (Scaphiopus couchii), indicating that endogenous regulation of antioxidants may reduce the susceptibility of muscle tissue to the effects of oxidative damage (13). In typical mammalian muscle disuse models the opposite trend has been observed, with a number of studies having documented skeletal muscle wasting despite the induction of defense mechanisms against oxidative stress (including increased Nrf2 transcription) (5,9,26). However, a more definitive understanding of the role for the Nrf2-regulated antioxidant response in estivating C. alboguttata will require additional research, as we found other cytoprotective genes (gstp1, dnajb5) regulated by Nrf2 to be suppressed.…”
Section: Nrf2-mediated Oxidative Defensesupporting
confidence: 61%
See 1 more Smart Citation
“…Similar results have been found in estivating toads (Scaphiopus couchii), indicating that endogenous regulation of antioxidants may reduce the susceptibility of muscle tissue to the effects of oxidative damage (13). In typical mammalian muscle disuse models the opposite trend has been observed, with a number of studies having documented skeletal muscle wasting despite the induction of defense mechanisms against oxidative stress (including increased Nrf2 transcription) (5,9,26). However, a more definitive understanding of the role for the Nrf2-regulated antioxidant response in estivating C. alboguttata will require additional research, as we found other cytoprotective genes (gstp1, dnajb5) regulated by Nrf2 to be suppressed.…”
Section: Nrf2-mediated Oxidative Defensesupporting
confidence: 61%
“…Lipids are still likely to be an essential fuel source during periods of estivation and/or fasting in C. alboguttata, although the liver and fat bodies are the most likely organs contributing to fatty acid metabolism, rather than skeletal muscle (22). Dramatic downregulation of energy metabolism pathways have been documented in clinical models of muscle disuse (5,6). Evidence suggests there is a shift in fuel metabolism away from fat oxidation toward an increased reliance on glucose, and that fat accumulates in atrophied muscles in place of muscle protein (reviewed in Ref.…”
Section: Energy Metabolismmentioning
confidence: 99%
“…Moreover, hindlimb unloading and casting caused, in skeletal muscle, an increase of LC3 ratio (LC3II/I) [54,60], a marker of autophagy activation. Data in human are scarce and less consistent [114]. All together, the results suggest that autophagy plays a role in skeletal muscle loss during immobilization.…”
Section: Cellular Mechanisms Involved In Immobilization-induced Skelementioning
confidence: 54%
“…Other proteomic studies investigated the plasticity of the muscle tissue proteome from human biopsies over a variety of clinically observed situations. Brocca and colleagues quantified proteome changes due to disuse using 2D electrophoresis and found myofibrillar proteins, metabolic enzymes, and antioxidant defense systems down‐regulated after 35 days of bed rest 19. Staunton and coworkers characterized proteome changes due to age‐dependent muscle loss and detected changes in muscle metabolism, ion handling, and the cellular stress response as a function of aging 20.…”
Section: Introductionmentioning
confidence: 99%